Association between elimination disorders and abusive maternal attitudes. (May 2016) - Alpaslan, Ahmet Hamdi; Koçak, Uğur; Avci, Kadriye; Güzel, Halil Ibrahim
Abstract: Objective: Enuresis and encopresis, both conditions are very distressful to children and their family members and it is responsible for significant social and psychological consequences in children and adolescents. The present study aims to determine the rate of abusive maternal attitudes towards children and adolescents with elimination disorders (EDs) and to investigate the maternal psychological and socio-cultural factors associated with abusive parenting attitudes. Method: N = 180 children with ED were included in the study. Family Assessment Device (FAD), and Symptom Check List (SCL-90-R) were administered to mothers. Results: Our results indicated that prevalence of abusive maternal attitudes in our sample was 73.8%. Children and adolescents with ED who live with low-educated parents ( p = 0.008), low socio economic status ( p = 0.014), and in cases with living in a large or divorced family ( p = 0.014), disorganized or chaotic families can be considered a population at risk ( p < 0.05), since it is more likely that they suffer more severe abusive maternal attitudes. Conclusion: Present study showed high rates of abusive parenting attitudes in cases of EDs in a sample of Turkish children and adolescents. Further research on the etiological and therapeutic importance of the family in the case of ED referred to a psychiatry clinic should be carried out. Highlights: Child abuse is a serious problem with complicated reasons and tragic results. Abusive maternal attitudes towards children and adolescents with elimination disorders assessed in a clinical sample. The prevalence of abuse in our sample was 73.8%. Generally, parents in our society do not consider enuresis or encopresis, as a medical disorder.